2021
DOI: 10.1017/s1041610221001459
|View full text |Cite
|
Sign up to set email alerts
|

212 - Involvement, Worries and Loneliness of Family Caregivers of People with Dementia during the COVID-19 Visitor-ban in Long-term Care Facilities

Abstract: BackgroundTo prevent COVID-19 from spreading in long-term care facilities (LTCFs), the Dutch government took national restrictive measures, including a visitor-ban in LTCFs between mid-March and May 2020.Physical visits were replaced by alternatives as telephone or video calls. This study examines the relationship between the involvement of family caregivers (informal caregivers, ICs) of people with dementia (PwD) living in LTCFs and IC mental health during the visitor-ban. Furthermore, we examine whether this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Prins and colleagues (2021) [ 46 ] wanted to investigate whether the impact of the protective measures on relatives was linked to relatives’ resilience and pre-pandemic visit frequency. The authors defined resilience as a personal characteristic which serves as a protective barrier against developing certain psychological problems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prins and colleagues (2021) [ 46 ] wanted to investigate whether the impact of the protective measures on relatives was linked to relatives’ resilience and pre-pandemic visit frequency. The authors defined resilience as a personal characteristic which serves as a protective barrier against developing certain psychological problems.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a study insisted on a heightened burden for relatives, because they could not engage in the care they were giving before the pandemic. Indeed, one study found that relatives that visited more their residents before the pandemic suffered more from the lockdown than relatives who visited their residents less often [ 46 ]. Qualitative studies exploring how relatives experienced the protective measures in nursing homes also corroborate their impact on the overall wellbeing of relatives.…”
Section: Discussionmentioning
confidence: 99%